Cultural Technologies (Taylor & Francis, 2025)
Cultural Technologies: Robots and Artificial Intelligence in the Performing Arts presents a diverse range of perspectives from leading scholars and artists on contemporary performing arts practices that engage with robotic and AI (artificial intelligence) technologies. In Part One, ""Robot/AI Cultures and Performing Arts Practices,"" contributors discuss how cultural understandings of robots and AI influence the audience’s reception of performance works that feature such technologies and inspire artistic innovation. The chapters in Part Two, ""Performing Arts Cultures and Robots/AI Developments,"" explore how theories and practices of the performing arts can engender critical dialogue on matters of cultural difference concerning culturally non-specific (though implicitly Western) framings of robotic and AI technologies within science and engineering contexts. Reorienting the conversation around robotics and AI in the performing arts to place culture at its centre, Cultural Technologies: Robots and Artificial Intelligence in the Performing Arts offers thought-provoking analyses for advanced undergraduates, researchers, and performing arts practitioners interested in the relationships between music, theatre, and dance, and cutting-edge robotic and AI technologies.